The Use of Peer Tutoring to Improve the Reading Skill of Seventh-Grade Students at SMPN 4 Tanjung - Anggi Sasmita; I Made Sujana; Kurniawan Apgrianto; Ahmad Junaidi (Journal of English Education Forum (JEEF), 2026)
Developing reading competence among junior high school students remains a persistent challenge in EFL contexts, particularly when conventional instruction fails to accommodate diverse learner needs. This study examined whether a peer tutoring approach could produce measurable gains in reading skill among seventh-grade students at SMPN 4 Tanjung. A quasi-experimental pre-test/post-test control group design was employed, involving 60 students distributed equally across an experimental class (VII-1, n=30) and a control class (VII-2, n=30). Over a period of four to six weeks, the experimental class participated in structured peer tutoring sessions, while the control class continued to receive teacher-led conventional instruction. Reading ability was assessed through narrative text comprehension tasks administered at the start and end of the intervention. Results revealed that the experimental group's mean score climbed from 58.33 to 73.33, whereas the control group's mean moved from 59.13 to 66.88. A paired-sample t-test confirmed within-group improvement in the experimental class (sig. = 0.000, p < 0.05), and an independent-sample t-test established a significant between-group difference at post-test (sig. = 0.000, mean difference = 15.03). These outcomes indicate that peer tutoring is a viable and effective instructional strategy for fostering reading development in secondary EFL settings.